RELEVANSI NILAI BUDAYA JAWA NOVEL KARTINI KARYA ABIDAH EL KHALIEQY DAN IMPLIKASINYA DENGAN PEMBELAJARAN SASTRA - Rr. Sulistyawati; Anisah Lestari (Akrab Juara : Jurnal Ilmu-ilmu Sosial, 2019)
The value of Javanese Culture in Novel Kartini by Abidah El Khalieqy and the Implications for Learning Appreciation of Indonesian Literature in High School. This study aims to determine the value of Javanese culture contained in Kartini's novel by Abidah El Khalieqy and its implications for literary appreciation learning in high school. Data from this study is the use of the Kartini novel by Abidah El Khalieqy. This research is classified as qualitative research. In this study the objects studied by the authors are: (1) intrinsic elements which include the theme, setting, plot, character and characterization, mandate, point of view and style of language. (2) The value of Javanese culture relates to various Javanese cultures such as literature, language, traditional ceremonies, arts, architecture, culinary, traditional clothing. (3) The dominant Javanese hierarchy emerged which was then analyzed using Javanese cultural theory. The results of the research conducted by the author indicate that many different Javanese cultures are contained in the novel. The emergence of these various cultures is none other because it is influenced by the background used in the novel, namely in Jepara, Central Java.